Evaluasi Penggunaan Obat Antitiroid Pada Pasien Hipertiroid di RSUP Dr. M. Djamil Padang, Indonesia - Dian Ayu Juwita; Suhatri Suhatri; Risa Hestia (Jurnal Sains Farmasi & Klinis, 2018)
Hyperthyroidism is the second largest hormonal disease in Indonesia after diabetes mellitus. The most common cause of hyperthyroidism is Graves’ disease. Untreated in hyperthyroid patients will causes decreased patient quality of life, atrial fibrillation and osteoporosis. Therefore need a therapy to control thyroid hormone levels in the normal range, one of them with antithyroid drugs. This study aims to determine the patterns of antithyroid use and evaluate the appropriateness use of antithyroid drugs in patients hyperthyroidism include precise indications, precise medications, precise patients and appropriate doses. This study is a descriptive study that retrospective data collection using patient medical records during the period January-December 2015 in Polyclinic Dr. M. Djamil hospital Padang. The number of patients who fulfills  the inclusion criteria are 175 patients. Antithyroid drugs used in patients with hyperthyroidism are PTU (82,75%) and thyrozol (17,25%). The results showed that inappropriate indication and inappropriate drug was not found, while there were 13 patients (7,43%) with an inappropriate dosage regimen and 1 patients (0,57 %) with inappropriate patient.